PERSEPSI KONSUMEN TERHADAP KUALITAS PELAYANAN DI BENGKEL MOTOR AHASS GLOBAL JAYA PERKASA PEKANBARU - Alfiori, Jenifer; Suarman, Suarman; RM Riadi, RM Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This research aims to know the perception of consumers to the quality of service in the motorcycle workshop AHASS Global Jaya Perkasa Pekanbaru. This research uses a descriptive analysis method to describe the consumer's perception of service quality at AHASS Global Jaya Perkasa Motorcycle Workshop. Sampling techniques using aksidental sampling technique is the determination of the sample based on coincidence, anyone who happens to meet the consumers of the motorcycle workshop AHASS Global Jaya Perkasa Pekanbaru so that researchers can Use it as a sample when viewed by the person who happens to be found suitable as a data source. Research instruments using poll. The results showed that consumer perception of the quality of service provided by AHASS Global Jaya Perkasa in general in good category. Consumer perception of service quality is supported by several indicators such as reliability, responsiveness, assurance, empathy and physical evidence.Key Words: Quality of service, AHASS Global Jaya Perkasa.